MEMBANGUN FONDASI HAFALAN SEJAK DINI: STRATEGI GURU DALAM MENGATASI KESULITAN HAFALAN AL-QURAN PADA SISWA DI SD MUHAMMADIYAH 12 PAMULANG - Bella Dwi Pertiwi; Mochamad Daffa Akmal (STKIP Subang, 2026)
This study is motivated by various challenges faced by lower-grade elementary students in memorizing the Qur’an, including limited concentration, inadequate Qur’anic reading skills, low learning motivation, and external factors such as dense academic schedules and minimal parental involvement. The purpose of this research is to describe in depth the strategies employed by tahfidz teachers to overcome memorization difficulties among early-grade students at SD Muhammadiyah 12 Pamulang. The research adopts a qualitative approach with a case study method to capture contextual and comprehensive insights. Data were collected through observations, in-depth interviews with tahfidz teachers, homeroom teachers, vice principals, students, and parents, as well as documentation. Data analysis involved data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation. The findings reveal that tahfidz teachers implement the talaqqi method as the primary approach, complemented by structured tasmi’ and muroja’ah activities. Teachers also apply personal approaches, continuous motivational support, and an educative reward and punishment system. In terms of learning media, strategies include grouping students based on memorization ability and utilizing audio-visual tools such as PowerPoint, murotal recitations, voice notes, and WhatsApp group communication. Indicators of success include increased quantity of memorization, improved recitation quality in accordance with tajwid and makhraj rules, and students’ ability to overcome memorization stagnation.